2008
DOI: 10.1542/peds.2007-1786
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled Trial of a Best-Practice Individualized Behavioral Program for Treatment of Childhood Overweight: Scottish Childhood Overweight Treatment Trial (SCOTT)

Abstract: BACKGROUND:Electronic cigarette (e-cigarette) use is common among youth, and there are concerns that e-cigarette use leads to future conventional cigarette use. We examined longitudinal associations between past-month cigarette and e-cigarette use to characterize the stability and directionality of these tobacco use trajectories over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
141
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(156 citation statements)
references
References 36 publications
14
141
1
Order By: Relevance
“…Results were largely similar, for cost and health outcomes, between the two school years and between the obese and overweight and obese groups (web reference 5). At a cost of d100 per child, similarly to the cost estimated by Hughes et al, 25 all of the intervention effect sizes become cost saving within the lifetime of the children if future treatment costs are not discounted (Table 3). For a BMI SDS reduction of À0.03, the cost of the intervention would never become cost saving for interventions over d200.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Results were largely similar, for cost and health outcomes, between the two school years and between the obese and overweight and obese groups (web reference 5). At a cost of d100 per child, similarly to the cost estimated by Hughes et al, 25 all of the intervention effect sizes become cost saving within the lifetime of the children if future treatment costs are not discounted (Table 3). For a BMI SDS reduction of À0.03, the cost of the intervention would never become cost saving for interventions over d200.…”
Section: Resultsmentioning
confidence: 82%
“…With one exception, 25 all studies suggested a trend for a relative reduction in BMI SDS in the intervention group at 6 or 12 months (Figure 2). At 12 months, the median effect on BMI SDS was À0.13 (ref.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…There is no evidence that preventing childhood obesity will reduce subsequent adult obesity, which is where virtually all health consequences and costs lie, and the evidence for efficacy, effectiveness or cost-effectiveness of interventions for childhood obesity is weak, lacking or negative. 14,15 We can learn from these studies directed at children, and build on successful elements,, but the focus looks fundamentally flawed.…”
mentioning
confidence: 99%